A comparative analysis of health status of international migrants and local population in Chile: a population-based, cross-sectional analysis from a social determinants of health perspective - Isabel Rada; Marcela Oyarte; Báltica Cabieses (BMC, 2022)
Abstract Background During recent decades intraregional migration has increased in Latin America. Chile became one of the main receiving countries and hosted diverse international migrant groups. Evidence have suggested a healthy migrant effect (HME) on health status, but it remains scarce, controversial and needs to be updated. This study performed a comprehensive analysis verifying the existence of HME and its association with social determinants of health (SDH). Methods We analyzed data from the Chilean National Socioeconomic Characterization Survey (CASEN, version 2017). Unadjusted prevalence of health status indicators such as negative self-perceived health, chronic morbidity, disability, and activity limitations were described in both international migrants and local population. Adjusted associations between these outcomes and sets of demographics, socioeconomic, access to healthcare, psychosocial and migration-related SDH were tested using multivariate logistic regression in each population. The HME for each health outcome was also tested using multivariate logistic regression and sequentially adjusting for each set of SDH (ref = Chilean). Results International migrants had lower unadjusted prevalence of all health indicators compared to Chileans. That is, unadjusted analysis revealed an apparent HME in all health outcomes. Age, unemployment, and health care system affiliation were associated with health outcomes in both populations. Psychosocial determinants were both risk and protective for the analysed health outcomes. After adjustment for each set of SDH, the immigrant health advantage was only significant for chronic morbidity. Being migrant was associated with 39% lower odds of having chronic diseases compared to locals (OR: 0.61; 95% CI: 0.44-0.84; P = 0.0003). For all other outcomes, HME disappeared after adjusting by SDH, particularly unemployment, type of health system and psychosocial factors. Conclusions Testing the HME in Chile revealed an advantage for chronic morbidities that remained significant after adjustment for SDH. This analysis shed light on health disparities between international migrants and local population in the Latin American region, with special relevance of unemployment, type of health system and psychosocial SDH. It also informed about differential exposures faced during migration process that could dissolve the HME over time. Evidence from this analytical approach is useful for informing health planning and intersectoral solutions from a SDH perspective.